Performance evaluation of a gas (butane) fired oven (2001)
A gas-fired oven for commercial production of bread was designed and constructed using locally available material and was subjected to various tests to come out with its performance characteristics. Its performance was evaluated arid then compared with respect to the total time required to bake a specified mass of white flour dough using the gas oven with that used by clay wood fired oven for the same mass of white flour dough. The outcome of the test result indicated that the maximum temperature attained by the oven was 400°C with the gas control valves at close to the maximum point (without load). This temperature was attained seven minutes after firing the oven. The clay wood fired oven tested attained a peak temperature of 280°C one hour after it was fired. White flour dough of mass 0.2kg was baked in the gas fired oven in thirty nine minutes (first load), this corresponds to the total baking time. The same unit mass of dough was baked in the wood fired oven in a total baking time of eight-five minutes. A test carried out on the insulating machine, sawdust, showed that it minimized the heat loss from the oven by maintaining a high temperature gradient between the inside wall and the outer wall of the oven. The preliminary economic analysis of the cost of production of the oven and the cost of fuel showed that is cost effective and viable.